The pleiotropic SEPALLATA‐like gene OsMADS34 reveals that the 'empty glumes' of rice (Oryza sativa) spikelets are in fact rudimentary lemmas. Issue 2 (24th December 2013) - Lin, Xuelei; Wu, Feng; Du, Xiaoqiu; Shi, Xiaowei; Liu, Yuan; Liu, Shujun; Hu, Yuxin; Theißen, Günter; Meng, Zheng
Summary: The single floret of the rice ( Oryza sativa ) spikelet is subtended by a pair of enigmatic organs usually termed 'empty glumes' or 'sterile lemmas'. As the identity of these organs remains essentially unknown, we refer to them as 'organs of unknown identity' (OUIs). Here we present a novel mutant of the rice SEPALLATA ‐like gene OsMADS34 which develops, in addition to disorganized branches and sterile seeds, elongated OUIs. The function and evolution of OsMADS34 were studied. Morphological and molecular markers indicate that the elongated OUIs have adopted lemma identity. Evolutionary analyses show that the ancestral genes of the OsM34 subclade evolved under positive selection, and that three specific motifs occur in the C‐terminal region of proteins in the OsM34 subclade. Yeast two‐hybrid assays revealed that the C‐terminal region of OsMADS34 plays a crucial role in mediating protein interactions. Sequence analyses for the wild rice Oryza grandiglumis which has elongated OUIs revealed the association of OsMADS34 functionality with OUI identity. Our findings support the hypothesis that OUIs originated from the lemmas of degenerate florets under the negative control of OsMADS34 . As OUIs neither are homologues to glumes nor have the identity of lemmas any more, but originated from these organs, we suggest calling them 'rudimentary lemmas'.